Are More Proficient Readers More Strategic? A Case Study of Four Taiwanese EFL University Students (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
The article presents the results, interpretations, and potential pedagogical implications of an experimental case study that explored the beliefs and actual use of reading strategies of four Taiwanese EFL university students. The emphasis of the qualitative analysis is put on what the participants effectively do rather than what they believe they do, something that many studies in the field overlook. In addition, the study investigated the interplay between reading strategy use and reading proficiency. The research triangulates the introspective data with the products of participants’ task activity. The participants were asked to fill out a self-reporting questionnaire. After a few days, they performed a reading task accompanied by the think-aloud protocol, took a comprehension test, and were interviewed. The study revealed that participants’ perceptions of their reading strategy use and the actual use were not always aligned. More importantly, the study findings indicate that the variety, frequency, and appropriateness of the actual use of reading strategies positively correlated with the participants' reading and general linguistic proficiency levels. Pedagogical implications and suggestions for further research are discussed, as well as the current study's limitations.